1998
DOI: 10.1146/annurev.ento.43.1.701
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Transgenic Insecticidal Cultivars: Integrating Pest Genetics and Ecology

Abstract: This review examines potential impacts of transgenic cultivars on insect population dynamics and evolution. Experience with classically bred, insecticidal cultivars has demonstrated that a solid understanding of both the target insect's ecology and the cultivar's performance under varied field conditions will be essential for predicting area-wide effects of transgenic cultivars on pest and natural enemy dynamics. This experience has also demonstrated the evolutionary capacity of pests for adaptive response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
1,196
2
74

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,237 publications
(1,284 citation statements)
references
References 106 publications
12
1,196
2
74
Order By: Relevance
“…Previous research has shown that the dominance is a primary determinant of the rate of the resistance evolution (Comins 1977a,b; Mani 1985; Alstad and Andow 1995; Gould 1998; Ives and Andow 2002; Tabashnik et al. 2004, 2008; Ives et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown that the dominance is a primary determinant of the rate of the resistance evolution (Comins 1977a,b; Mani 1985; Alstad and Andow 1995; Gould 1998; Ives and Andow 2002; Tabashnik et al. 2004, 2008; Ives et al.…”
Section: Discussionmentioning
confidence: 99%
“…Applying multiple toxins has been considered as a way to delay resistance evolution, either by using them simultaneously (e.g., pyramiding or mixture strategy (Mani 1985; Caprio 1998; Gould 1998; Roush 1998; Ives et al. 2011)) or sequentially (e.g., rotation strategy, which is common in insecticide applications (Gould 1998)).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insect resistance may become the largest impediment to the successful deployment of Bt crops. One effective way of lowering the selection pressure is by restricting the expression of Bt proteins to the tissues susceptible to insect damage (Gould, 1998;Frutos et al, 1999). To reduce the amount of active entomocide that might help select for resistance allele(s) in a pest population, we tested whether the ST-LS1 promoter from potato could limit the expression of the cry2Aa2 coding sequence to green tissues in tobacco (N. tabacum cv.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant approach has involved the combination of a consistent and high expression level of the cry gene with the deployment of a refuge (Roush, 1996;Gould, 1998). A refuge is an area of non-GM crop that is placed either within a crop as a seed mixture (a multi-line approach) or as a separate block within close proximity.…”
Section: Will Gm Crops Lead To Superpests and Superdiseases?mentioning
confidence: 99%